The Development of Anaphora Resolution at the Syntax-Discourse Interface: Pronominal Subjects in Greek Learners of Spanish - Lozano, Cristóbal (Journal of psycholinguistic research, 2018)
This study explores the development of anaphora resolution (AR) in late sequential bilinguals, namely, adult Greek learners of Spanish at three proficiency levels (intermediate, lower advanced, upper advanced). The use of an overt/null pronominal subject anaphor is investigated in three discourse contexts: topic-continuity (a single antecedent requiring a null pronoun), contrastive-focus (two same-gender potential antecedents requiring an overt pronoun to avoid ambiguity) and emphatic (three same-gender potential antecedents showing unclear preference for either overt or null pronoun). Crucially, AR behaves similarly in Greek and Spanish. Results from an offline contextualised acceptability judgement task show that similarity between the learner’s first (L1) and second (L2) languages does not necessarily facilitate the learning task. Even very advanced learners show deficits, which are selective since not all discursive contexts are equally affected. The results are better accounted for by general pragmatic economy principles: Learners prefer being redundant (overuse of overt pronouns in topic-continuity contexts) to ambiguous (acceptance of null pronouns in contrastive-focus contexts). Such tolerance for redundancy may reflect a more general pragmatic tendency, as also reported in child L1 development, adult L2 development and also in native grammars.